2012
DOI: 10.1371/journal.pbio.1001324
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Asynchronous Release from Fast-Spiking Interneuron in Human and Rat Epileptic Neocortex

Abstract: Asynchronous GABA release occurs at output synapses of fast-spiking interneurons in human and rat neocortex and is elevated in epileptic tissues from both species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
75
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 63 publications
(81 reference statements)
5
75
0
Order By: Relevance
“…In the present study, we demonstrated that SynII deletion reduced IPSC amplitudes and prolonged the release kinetics in PV interneurons, which have a key role in the regulation of seizure propagation (Krook-Magnuson et al, 2013;Sessolo et al, 2015). Furthermore, extensive evidence links epilepsy with asynchronous activity of GABAergic synapses through tonic inhibition (Jiang et al, 2012;Pandit et al, 2013;Medrihan et al, 2015). We demonstrated here that SynII maintains the asynchronous release component at CCK interneurons, which are thought to contribute to vulnerability of neuronal networks to seizure activity (Wyeth et al, 2010;Lee and Soltesz, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we demonstrated that SynII deletion reduced IPSC amplitudes and prolonged the release kinetics in PV interneurons, which have a key role in the regulation of seizure propagation (Krook-Magnuson et al, 2013;Sessolo et al, 2015). Furthermore, extensive evidence links epilepsy with asynchronous activity of GABAergic synapses through tonic inhibition (Jiang et al, 2012;Pandit et al, 2013;Medrihan et al, 2015). We demonstrated here that SynII maintains the asynchronous release component at CCK interneurons, which are thought to contribute to vulnerability of neuronal networks to seizure activity (Wyeth et al, 2010;Lee and Soltesz, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In some hippocampal interneurons, asynchronous vesicle fusion is the predominant form of neurotransmitter release (Lu and Trussell, 2000;Hefft and Jonas, 2005;Ali and Todorova, 2010;Daw et al, 2010). In cortical interneurons, asynchronous release may play an important role in regulating epileptoform activity (Manseau et al, 2010;Jiang et al, 2012;Medrihan et al, 2015). In excitatory synapses, asynchronous release can generate larger and prolonged postsynaptic responses and perhaps play a role in potentiation and plasticity (Iremonger and Bains, 2007;Peters et al, 2010;Rudolph et al, 2011).…”
Section: An Overview Of the Synaptic Vesicle Cyclementioning
confidence: 99%
“…2A). GABAergic dysfunction in epilepsy may result in subtle alterations in inhibitory circuits [23,24] , and the down-regulation of GABAergic inhibition may cause epileptiform activity [25] . In ka inic acid (KA)-lesioned rats, the amplitude and conductance of both non-NMDA and NMDA components of excitatory postsynaptic currents (EPSCs) are signifi cantly reduced in stratum lacunosum-moleculare interneurons, but the rise-time of EPSCs is not signifi cantly changed [26] .…”
Section: Interneuron Fate and Functional Cor Relates In Epilepsymentioning
confidence: 99%